Valgus deformity of the distal tibia in children and adolescents with idiopathic flatfoot: Can it be predicted using 3D movement analysis? - Dussa, Chakravarthy Ugandhar; Dostal, Nadine; Böhm, Harald (Gait & Posture, 2025)
Background: Distal tibial valgus deformity, though common in various medical conditions, has not been extensively studied in idiopathic flatfoot. It clinically presents as hindfoot valgus, mimicking flatfoot deformity, and requires X-rays for detection. Severity is quantified using resting calcaneal angle and standing tibio-calcaneal angles (STCA), but their prognostic value for identifying distal tibial valgus deformity remains unclear. The use of routine invasive radiographs in idiopathic flatfoot is controversial as instrumented non-invasive gait analysis gains popularity for investigative purposes. Research question: This study aimed to determine the prevalence of distal tibial valgus deformity in children and adolescents with idiopathic flatfoot using radiography and to identify parameters assessed during standing or walking that predict this deformity. Methods: A retrospective study included outpatients aged 7–17 years with idiopathic flatfeet. Participants underwent clinical examination, foot and ankle X-rays, and instrumented 3-dimensional gait analysis. A lateral distal tibia angle (LDTA) < 86° indicated valgus deformity, with LDTA 86–92° considered normal. Two groups were analysed: ankle valgus (LDTA < 86°) and normal ankle (86–92°). STCA, ankle tilt, intermalleolar height difference (IMHD), and eight kinematic parameters were correlated with LDTA. Results: The study included 136 patients (mean age 11.5 years, SD=2.2). Sixty-three patients had ankle valgus (LDTA 83.8°, SD=1.7°), and 73 had normal ankles (LDTA 88.8°, SD=1.3°), showing a significant difference between groups (p < 0.001). STCA during standing was the best predictor, though it explained only 9 % of variance, limiting robust prediction. Significance: The prevalence of distal tibial valgus deformity was 42 % in idiopathic flatfoot cases, highlighting the necessity for routine ankle radiographs due to the inability to clinically suspect this deformity. Further studies should explore the biomechanical effects and their clinical implications for management.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Ankle tilt; Ankle X-rays; Distal tibial valgus deformity; Idiopathic flatfeet; Instrumented gait analysis; Intermalleolar height; Lateral distal tibial angle; LDTA; Standing tibio-calcaneal angle; STCA